Pesan Dakwah dalam Novel Negeri Lima Menara - Islamiyah, Anisatul (Jurnal Komunikasi Islam, 2015)
This study discusses the message of dakwah in the novel Negeri 5 Menara and how the delivery of messages of dakwah that exists in the novel. This study is a qualitative research using discourse analysis of Van Djik. Results of this study suggest that the propaganda message that exist in the novel covering aspects of aqidah and Shari'ah. In delivering a message, by using discourse analysis model of Van Dijk, found thematically that country title of novel Negeri 5 Menara depicts dreams of students who want to study in the major countries that have large towers. While the semantics, the author of this novel wants to represent that Islamic boarding schools are not inferior to public schools.